C reactive protein as a prognostic indicator of severity in patients with acute pancreatitis - Ganesh, Bharath Nayak; Setty, Srinivas Nanjangud Masana (International Surgery Journal, 2020)
Background: Acute pancreatitis ranges from a mild illness to a severe disease with high morbidity and mortality. Severity affects the treatment and outcome. The existing scoring systems for assessment of its severity require are time consuming and expensive. This study was an attempt to evaluate the effectiveness of C-reactive protein (CRP) as a prognostic indicator and a marker of severity of acute pancreatitis. Methods: This was a prospective observational study conducted between among 50 patients diagnosed with acute pancreatitis. The Ranson’s score and CTSI was calculated for these patients. CRP levels were measured 48 hours after the onset of symptoms. They were observed for the development of local and systemic complications, and outcome. These were compared with the CRP values. Pearson coefficient was used to study the correlation between the variables. A p value of less than 0.05 was considered to be statistically significant. Results: 30 of the 50 patients had no local complications. 14 patients (28%) had peripancreatic collection and 6 (12%) had pancreatic necrosis. 24 of the 50 patients had systemic complications (48%). 25 patients had mild disease and 25 had severe disease as evidenced by the Ranson’s score. These 25 patients with severe disease also had raised CRP (p<0.05). There was no statistically significant correlation between the CTSI and CRP values. 4 patients with CRP values more than 400 succumbed to the illness. Conclusions: CRP can serve as an inexpensive alternative to the conventional severity assessment methods for the prediction of severity and outcome of patients with acute pancreatitis.